Pierwsza palingenezja Ustawy XII tablic - Zabłocka, Maria (Prawo Kanoniczne, 1993)
It is hard to overstimate the importance o f the Twelve Table law framed in the fifth century B.C. Therefore there were several attempts to reconstruct its content. ’’Tripertita” of Aelius Catus could be considered the first palingenesis of this act.